A new high energy gamma-ray observatory in the southern hemisphere: The ALPACA experiment. (February 2020) - Calle, C.; Hibino, K.; Hotta, N.; Katayose, Y.; Kato, C.; Kato, S.; Kawata, K.; Kihara, W.; Ko, Y.; Kojima, H.; Mayta, R.; Miranda, P.; et al.
Abstract: The ALPACA experiment is a new international project between Bolivia and Japan. It is going to consist of an 83, 000 m 2 surface air-shower array and a 5, 400 m 2 underground water Cherenkov muon detector array, and the experimental site is at Mt. Chacaltaya plateau at an altitude of 4, 740 m. Its main target is to observe 100 TeV gamma rays and explore high-energy gamma-ray sources in the southern sky. This is because such high-energy gamma rays hold the key to identify the origin of cosmic rays at the knee region of the energy spectrum. So far many high-energy gamma-ray sources have been found in the southern sky. They are emitting gamma rays of several tens of TeV, so some of them could be PeVatrons which accelerate cosmic rays to PeV energy region in the Galaxy. By observing them in higher energy region, we will obtain new knowledge of cosmic-ray acceleration to the knee region, and discover new gamma-ray sources. As the prototype experiment of ALPACA, the ALPAQUITA experiment is now under construction. In a MC simulation, we found that ALPAQUITA has the ability of detecting bright gamma-ray sources in the southern hemisphere such as Vela X within 1 year.